Nonstate Warfare : The Military Methods of Guerillas, Warlords, and Militias - Biddle, Stephen D. (Book collections on Project MUSE., 2021)
"Armed nonstate actors have received increasing attention since September 11th, 2001, both from scholars and from policy makers and soldiers--and with this attention has come a vibrant debate about whether nonstate civil warfare and insurgency is the future of war, and if so, how it should be countered. Yet underlying these debates is one crucial shared assumption: that states and nonstate actors fight very differently. Biddle upturns this distinction in How Nonstate Actors Fight, examining actual military methods to show that many nonstate actors now fight more "conventionally" than many states. Rather than a dichotomy, Biddle frames nonstate and state methods along a continuum and presents a systematic theory to explain any given nonstate actor's position on this spectrum. His theory emphasizes how actors' internal politics - especially their institutional maturity and war aims - determine their military choices. In doing so, Biddle bridges to largely opposing groups of scholarship: materialists who assume that material and structural constraints will lead nonstates to prefer irregular warfare, and culturalists who see nonstate warmaking as connected to social norms. Biddle integrates both materialist and cultural considerations into this theory, but emphasizes internal politics as the chief determinant of how any actor will fight. The first four chapters present Biddle's theory, and the next five test is across a range of historical examples, from Lebanon to Iraq to Somalia to Croatia to the Vietcong"--